2021
DOI: 10.3892/etm.2021.10762
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on evodiamine, a bioactive alkaloid of Evodiae fructus: Focus on its anti‑cancer activity and bioavailability (Review)

Abstract: Evodiae fructus (Wu-Zhu-Yu in Chinese) can be isolated from the dried, unripe fruits of Tetradium ruticarpum and is a well-known traditional Chinese medicine that is applied extensively in China, Japan and Korea. Evodiae fructus has been traditionally used to treat headaches, abdominal pain and menorrhalgia. In addition, it is widely used as a dietary supplement to provide carboxylic acids, essential oils and flavonoids. Evodiamine (EVO) is one of the major bioactive components contained within Evodiae fructus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 140 publications
0
8
0
Order By: Relevance
“…Natural compounds and their derivatives exert anticancer effects via multiple mechanisms. In traditional herbal medicine, EF has been used for the treatment of headaches, abdominal pain, and menorrhalgia [ 31 ]. Through activity screening and mechanistic study, evodiamine was identified as one of the major bioactive components of EF against various types of cancers including colon cancer [ 32 ], hepatocellular carcinoma (HCC) [ 33 ], lung cancer [ 34 ], and melanoma [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Natural compounds and their derivatives exert anticancer effects via multiple mechanisms. In traditional herbal medicine, EF has been used for the treatment of headaches, abdominal pain, and menorrhalgia [ 31 ]. Through activity screening and mechanistic study, evodiamine was identified as one of the major bioactive components of EF against various types of cancers including colon cancer [ 32 ], hepatocellular carcinoma (HCC) [ 33 ], lung cancer [ 34 ], and melanoma [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…T.G.Hartley, and is one of the most important components of the Chinese herb 'Wu-Zhu-Yu' (50). EVO has been revealed to exert its anticancer effects by inhibiting cell growth, invasion, and metastasis, and inducing apoptosis in cancer cells in colon cancer, lung cancer, hepatocellular carcinoma, and melanoma (51). Mechanisms of the anticancer effects of EVO in ARO ATC cells include the inhibition of cell proliferation, increase in DNA fragmentation, induction of apoptosis, and G2/M phase arrest.…”
Section: Evodiamine (Evo)mentioning
confidence: 99%
“…The indole alkaloid evodiamine (Evo) is one of the main bioactive components of Evodia rutaecarpa . It has been used for several years in TCM for treating cancer, obesity, inflammation, cardiovascular, and Alzheimer’s diseases [ 116 , 117 ]. The main symptoms of functional gastrointestinal illnesses are motility dysfunction and abdominal pain.…”
Section: Natural Compounds With Effects On Voltage-gated Calcium Chan...mentioning
confidence: 99%